A study on the prevalence of HCV genotypes and the effect of direct-acting antiviral therapy on clinical and laboratory parameters in HCV-Infected patients at a tertiary care center in North India - S Muhammed Shahanas; Rajeev Verma; Kanishka Kumar; Manisha Verma; Deepak Chandra Srivastavsa; Priyanka Budhwani (Wolters Kluwer Medknow Publications, 2024)
Background: The purpose of this study was to investigate the prevalence and distribution of different HCV genotypes, as well as to evaluate clinical and laboratory parameters in HCV-infected patients before and after DAA treatment. Material and Methods: An open-label prospective study was conducted on 50 HCV-infected individuals. The HCV-infected patients underwent a baseline evaluation with complete history, examination, and other clinical investigations. These patients received the appropriate DAA according to the genotype for 3 months. At the end of 3 months, these patients were again evaluated clinically. Results: The majority of instances were among younger age groups. Genotype 3 (66%) was the most common. There was a statistically significant difference found in clinical parameters regarding total bilirubin (p=0.008), SGOT (p=0.001), SGPT (p=0.035), ALP (p=<0.001) and Blood Urea Nitrogen (p = 0.004). When 1a vs 1b intragroup comparison was drawn, there was a significant mean difference found in SGOT (p value= 0.053) and Creatinine (p=0.050) parameters while rest shows no significant difference when associated. In the comparison of 1a vs 3 or 4, none of the parameters shows significant difference while; when 1b vs 3 or 4 comparison was laid out, SGOT and Creatinine was found near to significant. Conclusion: This study concludes that with the availability of DAAs, highly effective, short-duration, and safe regimens have created better outcomes for patients with HCV infection, especially in those groups where SVR was low with prior therapies or in those where IFN-based treatment strategies were contraindicated.